Return to competition in elite judo athletes after arthroscopic soft tissue stabilization with selective augmentation - Hamada, H.; Sugaya, H.; Takahashi, N.; Tokai, M.; Matsuki, K. (Journal of Bodywork and Movement Therapies, 2025)
Background: Shoulder instability is one of the most common problems in judo. Some studies have examined outcomes of shoulder stabilization in judo athletes. While open procedures yield acceptable results, arthroscopic stabilization has yielded poor outcomes or involved small sample sizes. For >20 years, the authors have treated competitive judo athletes with soft tissue Bankart repair and soft tissue augmentation, such as rotator interval closure.